Addition of Sodium Dodecyl Benzene Sulfonate as Surfactant in Water-based Nanofluid with Al2O3 particles for Quench Medium Application - Fatih Abdul Syauqi; Achmad Fauzi Trinanda; M. Asykar Bangun; Ghiska Ramahdita; Sri Harjanto; Wahyuaji Putra (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
Rapid cooling is an important step in the metal heat treatment industry to increase the materials hardness. To obtain this high cooling rate, good quality quench medium is a must. However, low thermal conductivity is a primary limitation in fluid used for this purpose. Nowadays, a higher thermal conductivity fluid are widely developed by using nanofluids. Nanofluids are created by suspending particles with average sizes below 100 nm in fluid base such as water, oil, diesel, ethylene glycol, etc. Aluminium oxide (Al2O3) can be used as mentioned particle because of its high thermal conductivity characteristic. In addition, the thermal conductivity of Al2O3 will increase with the decreasing of the particle size because the surface area of the particle increased.However, Most of the nanofluids with Al2O3 particle are prepared by using an ultrasonic stirring which is not stable for a longer time. Therefore, surfactant is needed to stabilize the nanofluid.In this research, 1 – 5% of sodium dodecyl benzene sulfonates (SDBS) was added as surfactant into 100 ml water-based nanofluid with 0.5% volume Al2O3. Commercial grade Al2O3 powder was used in the experiment and milled for 10 hours at 500 rpm. As for surfactant, a commercially available household bodycare product which contain SDBS was used. Initial result by Scanning Electron Microscope showed that the particle size after milling were more than 100 nm. This nanofluid was then used as quenching medium for S45C medium carbon steel which heated at 1000°C for 1 hour. Hardness and microstructure observation were conducted for the steel samples. From the hardness result, SDBS addition lower the hardness of quenched S45C sample to 568 HV, compared with 636 HV for nanofluid without SDBS. This mean that SDBS reduce the cooling rate of nanofluid quenchant.